Wall material used for a two-storey house at Parit Haji Talib (AAC block and sand lime brick) / Nur A’reesyia Mardhiah Norazemi - Norazemi, Nur A’reesyia Mardhiah (Universiti Teknologi MARA UiTM,Perak, 2022)
Wall is one of the most essential parts in the construction of a house or structure. It defines an area, carries the load, and serves as a safety barrier for its occupants. Many other function of a house's wall include weather protection and seclusion. A building is unfinished if it is without a wall. So, this report will go through the wall materials utilized in the construction of a bungalow house at H.S.(M) 903, MLO 34, Parit Haji Talib, Mukim Tanjong Sembrong, Batu Pahat, Johor that owned by En Adnan Bin Ismail. The objective of this report is to identify the method of bricklaying wall process. It is also to figure out the equipment and tools that used in the bricklaying wall process. This report will also explain about the problem and solution of using that material of wall construction. In addition, there are three methods of study for this report such as observation, interview and document review. For the findings of the study, the wall is the important component in construction. But, it is not easy to build a good wall without skilled workers because there are several alternatives ways utilized in a wall construction process.